Recent progress of perovskite-based electrolyte materials for solid oxide fuel cells and performance optimizing strategies for energy storage applications. (February 2022) - Hanif, Muhammad Bilal; Rauf, Sajid; Motola, Martin; Babar, Zaheer Ud Din; Li, Chang-Jiu; Li, Cheng-Xin
Highlights: A comprehensive review of perovskite-based electrolyte materials for SOFC has been provided. The selection of initial composition, dopants addition with critical challenges has been assessed. Performance optimizing strategies for energy storage applications were highlighted. The problems and future directions of dopants addition on SOFCs were critically analyzed. Abstract: Solid oxide fuel cells (SOFCs) are found to have potential application in energy conversion technology due to their characteristics i.e., good modularization, better fuel efficiency, and lesser toxic products (CO2, SOx, and NOx ). Mostly the electrolytic materials with ionic or protonic conductivity, undergo degradation at various operating conditions which must be prevented. Based on the above-mentioned problems, perovskites are considered as one of the wonderful classes of electrode and electrolyte materials with hydrocarbon fuels and retentivity of inherent stability at reducing/oxidizing atmosphere. In this review, recent developments in perovskite electrolyte materials of solid oxide fuel cells are summarized with prospects. Here, our main purpose is to deliver a brief tutorial corresponding to the structure, properties, and electrochemical behavior of perovskite-based electrolytes in test cells with various dopants together and inherited challenges regarding this material family. Several novel design strategies for the optimization of cell performance i.e., interface engineering, strain modulation, and defect engineering have been discussed in detail. In addition to this, a perspective has been proposed on the development routes or designs for perovskite oxide-based materials with high performance in energy conversion and storage applications as well as the way forward to cope with the challenges involved in the research route regarding the performance of each component. Graphical abstract: Image, graphical abstract